Experiment and analysis of the seed suction model for rice pneumatic seed metering device using DEM-CFD approach - Xing, He; Wang, Yuwan; Chen, Yuanbing; Yang, Ru; Bo, Xizhu; Zang, Ying (International Journal of Agricultural and Biological Engineering, 2025)
The model describing the forces acting on rice seeds within seed metering systems significantly impacts the design and structural parameters of rice pneumatic seed metering mechanisms. To formulate a mathematical representation of the device during seed suction, a DEM-CFD bidirectional coupling approach was utilized to simulate and model the seed-suction process. The dynamic behavior of rice seeds under the airflow at the suction port was examined, and force models for various seed-suction positions were developed. Simulation analyses were conducted under varying conditions, including different rotation speeds of the seed-suction plate and different levels of negative suction pressure. The effects of these variables on seed suction were investigated, leading to the development of a drag force model. Optimal seeding parameters and precision were determined from the simulation results. Verification and analysis were conducted through empirical experiments, and the optimal seeding performance was attained at a negative suction pressure of 1.6 kPa and a plate rotation speed of 30 r/min. The results indicated a seeding qualification rate of 95.7%, a reattachment rate of 2.4%, and a leakage suction rate of 1.9%. The simulation findings were consistent with experimental data, demonstrating that the seed-metering device satisfies the requirements for field seeding. Keywords: rice seeding, seed metering device, seed suction model, agricultural machinery, DEM-CFD DOI: 10.25165/j.ijabe.20251805.9422 Citation: Xing H, Wang Y W, Chen Y B, Yang R, Bo X Z, Zang Y. Experiment and analysis of seed suction model for rice pneumatic seed metering device using DEM-CFD approach. Int J Agric & Biol Eng, 2025; 18(5): 191–197.